Assessment of the ecological status of phytobenthos along the Black Sea coast of Georgia based on national environmental agency data for 2021 and 2023 - Gavardashvili, Givi; Bziava, Konstantine; Sönmez, Adem Yavuz; Supatashvili, Tamriko; Modebadze, Sopio (Marine Science and Technology Bulletin, 2025)
This study evaluates the ecological status of phytobenthic (benthic algal) communities along the Georgian Black Sea coast using monitoring data collected in 2021 and 2023 by the National Environmental Agency of Georgia. Monitoring encompassed multiple coastal sites representing a gradient from relatively undisturbed natural areas to urbanized and port-affected zones. Phytobenthic communities were assessed using standard bioindicator indices that integrate species richness, community structure, and the proportion of pollution-tolerant versus sensitive taxa. Results revealed clear spatial patterns: natural sites maintained high species richness and structural complexity, whereas urban and port-impacted areas exhibited reduced biodiversity, simplified community composition, and dominance of tolerant green algae. The decline of sensitive red and brown algae in impacted zones indicates localized eutrophication processes. Phytobenthos proved effective as bioindicators, reflecting both short-term pressures and longer-term ecological trends. These findings highlight the importance of conserving high biodiversity refugia, controlling nutrient inputs, and implementing management strategies to mitigate anthropogenic pressures. This research contributes to harmonized regional monitoring approaches and provides a scientific basis for sustainable management of Georgian Black Sea coastal ecosystems.